A new LC–MS/MS bioanalytical method for atenolol in human plasma and milk. (April 2017) - Phyo Lwin, Ei Mon; Gerber, Cobus; Song, Yunmei; Leggett, Catherine; Ritchie, Usha; Turner, Sean; Garg, Sanjay
Aim: A new sensitive LC–MS/MS method for the quantification of atenolol in human plasma and milk has been developed for clinical lactation studies.Methods & results: Atenolol and the internal standard, phenazone, were extracted from biological matrices by protein precipitation. A Phenomenex ® C-18 column and gradient chromatographic conditions were used for separation of the analyte, followed by detection with MS. Stability of samples was confirmed for atenolol in human plasma and milk for up to 3 months. Linearity range of 1–800 ng/ml (r 2 = 0.9995), the precision within 15% CV and the recovery of the analyte (80–100% range) were achieved.Conclusion: A new validated analytical method for atenolol in plasma and milk was developed.